Evolution of oxidative and structural characteristics of proteins, especially lipid transfer protein 1 (LTP1) in beer during forced‐ageing. (13th June 2019) - Cai, Linfei; Brennan, Charles S.; Yang, Huirong; Li, Wanying; Zhao, Haifeng
Summary: The evolution of oxidative and structural characteristics of proteins, especially lipid transfer protein 1 (LTP1), in beer during forced‐ageing was examined. The oxidative characteristics of beer and proteins were evaluated by DPPH radical scavenging activity and ABTS radical cation scavenging activity. Results showed that the levels of proteins, thiols, LTP1 and antioxidant activity decreased gradually. This was accompanied by the degradation of macromolecular proteins in beer during forced‐ageing. Results from circular dichroism (CD), Fourier‐transform infrared spectroscopy (FTIR), surface hydrophobicity ( S 0 ) and ζ‐potential further indicated that the secondary and tertiary structure of LTP1 changed drastically during forced‐ageing, with the reduction of the S 0, α‐helix and β‐sheet contents and the increase in negative ζ‐potential and random coil. Thus, the proteins, especially LTP1, might play important roles in maintaining oxidative stability of beer. Abstract : Evolution of oxidative and structural characteristics of proteins in beer during forced‐ageing.